1991
DOI: 10.1042/bj2730283
|View full text |Cite
|
Sign up to set email alerts
|

Post-translational alterations in newly synthesized cartilage proteoglycans induced by the glutamine analogue 6-diazo-5-oxo-l-norleucine. Time course of inhibition and recovery

Abstract: Incorporation of [35S]sulphate by cultures of matrix-free cells from chick embryo sterna in the presence of the glutamine analogue 6-diazo-5-oxo-L-norleucine (0.58 mM) was inhibited in a time-dependent manner to less than 15% of that in control cultures after 2 h. Characterization of the major cartilage proteoglycan synthesized under these conditions showed that it contained few, if any, normal-sized chondroitin sulphate chains and only about half of the normal complement of substituted serine residues. Subseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1991
1991
2002
2002

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Molecular analysis and morphological studies have confirmed the phenotype and genotype of these cells in that they produce cartilage-specific genes, and continue doing so for many days in culture without de-differentiating [29]. Chondrocytes have been shown to respond to various mechanical stimuli by an increase in gene expression and/or a rise in the rate of proteoglycan and collagen synthesis [6,15] Calcium may have a role in mediating these mechanical effects, as the calcium signaling pathway is shown to be involved in the process of mechanotransduction when other types of mechanical stimuli are used. Brighton et al have demonstrated that calcium signaling mechanism mediates the proliferative response of calvarial bone cells to mechanical stimulus in the form of biaxial strain [ 11.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular analysis and morphological studies have confirmed the phenotype and genotype of these cells in that they produce cartilage-specific genes, and continue doing so for many days in culture without de-differentiating [29]. Chondrocytes have been shown to respond to various mechanical stimuli by an increase in gene expression and/or a rise in the rate of proteoglycan and collagen synthesis [6,15] Calcium may have a role in mediating these mechanical effects, as the calcium signaling pathway is shown to be involved in the process of mechanotransduction when other types of mechanical stimuli are used. Brighton et al have demonstrated that calcium signaling mechanism mediates the proliferative response of calvarial bone cells to mechanical stimulus in the form of biaxial strain [ 11.…”
Section: Discussionmentioning
confidence: 99%